2012
DOI: 10.1116/1.4766318
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interaction of polymethylmethacrylate fragments with methyl isobutyl ketone and isopropyl alcohol

Abstract: Electron beam lithography of nanostructures using 2-propanol:water and 2-propanol:methyl isobutyl ketone as developers for poly-methylmethacrylate J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This is consistent with the rheological results stated above and exhibits the same R h trend in PMMA-g-NPs with IL systems. 43,44 In addition, compared to the simulation results of PMMA fragments with the same repeat units in some organic solvents, 56 the value of R g in our study is very close to but slightly lower than the reported data, which further confirms the reliability of our simulation.…”
Section: Resultssupporting
confidence: 87%
“…This is consistent with the rheological results stated above and exhibits the same R h trend in PMMA-g-NPs with IL systems. 43,44 In addition, compared to the simulation results of PMMA fragments with the same repeat units in some organic solvents, 56 the value of R g in our study is very close to but slightly lower than the reported data, which further confirms the reliability of our simulation.…”
Section: Resultssupporting
confidence: 87%
“…To evaluate the effect of the development process on adhesion, it is known that development is not a layer-by-layer linear dissolution process. 20,21 Instead, the solvent diffuses and penetrates below the top (recessing) surface and dissolves or swells the resist there. The situation is worse for low energy exposure because the under-exposed resist at the bottom is more susceptible to swelling/weakening by the solvent developer that has penetrated there.…”
Section: Resultsmentioning
confidence: 99%
“…Second, inclusion of explicit developer solvent molecule will be performed for improving the description of development process from the current dissoluble chain removal method, and several molecular/stochastic simulations will be a useful guideline for the modeling.…”
Section: Discussion: Pag Loading Effectmentioning
confidence: 99%